Workload Review Of The Performance Of Filling Officers To Meet The Time Standards For Providing Outpatient Medical Record Files At Imelda Hospital Medan - Karo Karo, Siddik; Mendrofa, Berthy Elsani (Jurnal Komputer Indonesia (Ju-Komi), 2023)
Workload is the volume of work results or records of work results. If the number of workers is small, while the workload is increasing, it will result in low work productivity and will affect the quality of hospital services to patients. Indonesian workers. The type of research used is descriptive quantitative. The data collection method used was interview guide. This research was conducted at Imelda Indonesian Workers General Hospital from May to September 2021. The population in this study were all 19 medical record employees. The sample used in this study were some of the medical record employees, totaling 4 people. From the results of the study, it was found that the number of filling officers at the Imelda General Hospital of Indonesian Workers was 4 people with the workload of officer A in providing medical record files as many as 356 documents with an average time of provision of 14.8 minutes, officer B in providing medical record files as many as 421 documents with an average time of provision of 17.1 minutes, officer C in providing medical record files as many as 291 documents with an average supply time of 12.1 minutes and officer D in providing medical record files as many as 359 documents with an average time of provision of 14 ,9 minutes. The conclusion is that the workload of filling officers at Imelda general hospital for Indonesian workers has a very strong influence on the average time of providing outpatient medical record files. Based on this, it is suggested to the hospital to carry out a workload analysis to determine the number of staff needs, especially in filling, and to motivate filling officers to increase the speed of providing medical record files.